Using Digital Media During the COVID-19 Pandemic Era: Good Online Program in Higher Education - Aziz Awaludin; Harun Joko Prayitno; Muhammad Izzul Haq (Universitas Muhammadiyah Surakarta, 2023)
This study aims at documenting the experience and perceptions of an Indonesian university professor in regard to teaching using digital media during the coronavirus disease 2019 (COVID-19) pandemic. Ample research has pointed out that the use of digital technologies can raise both potentials and challenges. This study examines the two contrasting perspectives by considering the current health disaster, the COVID-19 pandemic, which can add to the complexities of the virtual education in Indonesia. Research on virtual edu-cation in the context of Indonesian higher education during the pandemic is very limited and, thus, this study has gained its significance. We used qualitative methodology to approach this investigation with interview as the data collection technique and thematic analysis as its method of analysis. The results of this study present some key insights into the ways to integrate digital technologies within higher education instruction and what criteria to consider when selecting digital media. We argue that using digital technolo-gy helped educators facilitate teaching and learning regardless of the health crisis they were facing. This paper can be of use for educators in higher education to find ways in infusing digital media in their everyday instructions.